Factors Affecting Utilization of Health Services Among Elderly of Koshi Province, Nepal - Basnet, Saraswati; Silwal, Suvekshya; Thapa, Sheela (Rupantaran: A Multidisciplinary Journal, 2024)
Every country in the world is experiencing growth in the number and proportion of older persons. Aging is poised to become one of the most significant social transformations of the twenty-first century which affects all sectors of society. Aim of study was to assess factors affecting the utilization of health services among the elderly of Koshi province, Nepal. A quantitative descriptive cross-sectional study was conducted among 357 elderly. A multistage sampling technique was recruited for the selection of eight municipalities and wards for obtaining a representative sample from each ward. A semi structured interview schedule was used for data collection procedure. Descriptive statistics and inferential statistics were used after the normality test to measure the association of selected variables and utilization of health services. The study finding revealed that more than two-third (70.3) of the respondents was young old age. More than half of the respondents were female. Less than half (44.0%) of the respondents were hypertensive. A multivariate analysis revealed that the utilization of health services is higher among service holder elderly than non-service holder. The utilization health services by elderly were higher who had health insurance than who had not insurance service. The study concludes that only two-thirds of the elderly were satisfied with health insurance services facilities. Although One-thirds of elderly still not satisfied with the health insurance service facility so improve and easy access insurance service to elderly is essential.